2020
DOI: 10.1186/s13578-020-00414-2
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic fatty liver disease experiences accumulation of hepatic liquid crystal associated with increasing lipophagy

Abstract: Background: In the past 30 years, incidences of non-alcoholic fatty liver disease (NAFLD) has risen by 30%. However, there is still no clear mechanism or accurate method of anticipating liver failure. Here we reveal the phase transitions of liquid crystalline qualities in hepatic lipid droplets (HLDs) as a novel method of anticipating prognosis. Methods: NAFLD was induced by feeding C57BL/6J mice on a high-fat (HiF) diet. These NAFLD livers were then evaluated under polarized microscopy, X-ray diffraction and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 48 publications
0
2
0
1
Order By: Relevance
“…In this study, by quantitative estimation of both the phase difference and the ratio of amplitudes of the orthogonal polarization components of the light beam interacting with the cancer cell, the PSDHI localizes the strongest birefringence variation in the lipid droplets. Indeed, it has been previously reported that the ordered composition of LDs can alter the interaction with polarized light ( Reginato et al, 1985 ; Sturley and Hussain, 2012 ; Bautista et al, 2014 ; Li and Cheng, 2014 ; Ioannou et al, 2019 ; Coppola and Ferrara, 2020 ; Wang et al, 2020 ) and we demonstrated that it can be sensitively detected by PSDHI. The HepG2 cell map by both Raman and PSDHI imaging provided unequivocally correlations between the deut-Glc uptake, the localization of C-D signal in lipid droplets and the space-variant polarization quantitative information provided by PSDHI.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…In this study, by quantitative estimation of both the phase difference and the ratio of amplitudes of the orthogonal polarization components of the light beam interacting with the cancer cell, the PSDHI localizes the strongest birefringence variation in the lipid droplets. Indeed, it has been previously reported that the ordered composition of LDs can alter the interaction with polarized light ( Reginato et al, 1985 ; Sturley and Hussain, 2012 ; Bautista et al, 2014 ; Li and Cheng, 2014 ; Ioannou et al, 2019 ; Coppola and Ferrara, 2020 ; Wang et al, 2020 ) and we demonstrated that it can be sensitively detected by PSDHI. The HepG2 cell map by both Raman and PSDHI imaging provided unequivocally correlations between the deut-Glc uptake, the localization of C-D signal in lipid droplets and the space-variant polarization quantitative information provided by PSDHI.…”
Section: Discussionmentioning
confidence: 52%
“…The large difference in LDs abundance between cancer and WBCs must thus be assessed using a microscopy technique enabling acquisitions at video rate speed. It is known that the LDs are formed by highly packed and ordered arrays of cholesterols, triglycerides and phospholipids and exhibiting specific optical density and birefringence ( Reginato et al, 1985 ; Sturley and Hussain, 2012 ; Bautista et al, 2014 ; Ioannou et al, 2019 ; Wang et al, 2020 ). In order to detect these optical properties, we used a recently developed polarization-sensitive digital holographic imaging (PSDHI) that allows to measure with high sensitivity and velocity the modification of the state of polarization (SoP) of polarized light forward scattered by the sample and correlated with the Raman signals ( Coppola and Ferrara, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation